Scientific Method's Application Contexts for the Development and Evaluation of Research Skills in Higher-Education Learners - Patricia Vázquez-Villegas; Luis Alberto Mejía-Manzano; Juan Carlos Sánchez-Rangel; Jorge Membrillo-Hernández (MDPI AG, 2023)
The evolution of curricula in recent decades has given rise to multiple ways of teaching the task of experimental science, through which research skills are developed. In this learning gain process, teaching the systematized steps of the scientific method has been of invaluable help. In this study, we wanted to determine under what contexts of the last century the knowledge of the scientific method has encouraged the development of research skills in higher education learners. Through a literature review yielding nineteen empirical articles in the SCOPUS and Web of Science databases between 2000 and 2022, it was found that the scientific method is rarely mentioned and is more often referred to as a set of steps or structures to solve a problem, a challenge, or to carry out an investigation or an assigned task. Problem-solving and critical thinking were the two most-cited skills developed through the knowledge and practice of the scientific method. There are skills developed in theoretical classes and others that can be developed in practical courses such as laboratories or field work. A gap was found in the literature on using the scientific method and developing research skills in learners of non-science, technology, engineering, and mathematics (STEM) fields. The findings of this review lead studies to determine and compare whether effectively teaching students the scientific method improves their understanding and development of research skills in STEM and non-STEM areas.